An Insight of Employing of New Technologies in Conducting Online Assessment among Arabic School Teachersin Northern Malaysia - ZAINI, ABDUL RAZIF; SAHRIR, MUHAMMAD SABRI; HASSAN, YAAKOB; HAMAT, ZULKEFLI; RASHID, KHADIJAH KHALILAH ABDUL (The journal of contemporary issues in business and government, 2021)
This study is conducted to investigate the level of technological pedagogical content knowledge (TPACK) skill among Arabic school teachers in preparing online assessment for remote teaching and assessment prior to a trainingworkshoporganized by the Malaysian branch of Islamic World Educational, Scientific and Cultural Organization, ICESCO-KUIS and Islamic Education Unit, Ministry of Education, Malaysia. This research team has been conducting the TPACK training module among 75Arabic school teachers in Northern Malaysia on 28-29March, 2021 from the states of Kedah, Penang and Perlis in a hybrid mode of training, while only 69 of them responded to the survey after the workshop via Google Form. In addition, all participants were also responding to the open-ended survey during the workshop via Mentimeter.com. This research instruments were investigating the teachers’ knowledge about three essential components of TPACK, which include technology, content, and pedagogy as well their suggestions and feedbacks towards employing online assessment and effectiveness of conducted workshop. The findings are expected in contributing towards the understanding of the teacher’s level of knowledge in technology, pedagogy, and content among Arabic school teachers in Malaysia especially for preparing and conducting effective online teaching and assessment activities especially during the COVID-19 pandemic,Thestudy may also beneficialto other similar settings where the technology has not been effectively utilized by teachers in schools and home-based learning environment.